New version page

# UCLA MATH 31B - Practice Problems for Midterm 2

Pages: 17
Documents in this Course

## This preview shows page 1-2-3-4-5-6 out of 17 pages.

View Full Document
Do you want full access? Go Premium and unlock all 17 pages.
Do you want full access? Go Premium and unlock all 17 pages.
Do you want full access? Go Premium and unlock all 17 pages.
Do you want full access? Go Premium and unlock all 17 pages.
Do you want full access? Go Premium and unlock all 17 pages.
Do you want full access? Go Premium and unlock all 17 pages.

Unformatted text preview:

Practice Problems for Midterm 2(1) Compute the radius of convergence of the series∞Xn=14nn(x − 3)nSolution. We will determine the radius of convergence by applyingthe ratio test. We havelimn→∞4n+1n+1(x − 3)n+14nn(x − 3)n= limn→∞4(x − 3)1n+11n= limn→∞4(x − 3)n + 1n= 4(x − 3)since limn→∞nn+1= 1. By the ratio test, the seriesP∞n=14nn(x − 3)ndiverges if |4(x − 3)| > 1 and converges when|4(x − 3)| < 1 ⇐⇒ |x − 3| <14,so the radius of convergence is14.(2) Compute the radius of convergence of the series∞Xn=1xn2nn2Solution. We havelimn→∞xn+12n+1(n+1)2xn2nn2= limn→∞x2·1(n+1)21n2= limn→∞x2nn + 12=x212since limn→∞nn+12= 1. By the ratio test, the series diverges if|x2| > 1 and converges whenx2< 1 ⇐⇒ |x| < 2,so the radius of convergence is 2.(3) Compute the radius of convergence of the series∞Xn=12xn3nn2Solution. We havelimn→∞2xn+13n+1(n+1)22xn3nn2= limn→∞x3·1(n+1)21n2= limn→∞x3nn + 12=x3since limn→∞nn+12= 1. By the ratio test, the series diverges if|x3| > 1 and converges whenx3< 1 ⇐⇒ |x| < 3,so the radius of convergence is 3.(4) Calculate the sum∞Xn=1(−1)n2n+13nSolution. This is a constant multiple of a geometric series. Factoringout the 2, we obtain∞Xn=1(−1)n2n+13n= 2∞Xn=1(−1)n2n3n.3Note(−1)n2n3n= (−23)n, so this is equal to2∞Xn=1−23n.We factor out−23and then apply the geometric series formula since|−23| < 1.2−23∞Xn=0−23n= −43·11 − (−23)= −43(1 +23)= −45.(5) Calculate the sum∞Xn=3(−1)n3n+14nSolution. Factoring out the 3, we obtain∞Xn=3(−1)n3n+14n= 3∞Xn=3(−1)n3n4n.Note(−1)n3n4n= (−34)n, so this is equal to3∞Xn=3−34n.4We factor out−343= −2764and then apply the geometric seriesformula since |−34| < 1.3−2764∞Xn=0−34n= −8164·11 − (−34)= −8164(1 +34)= −81112.(6) Calculate the sum∞Xn=02n+ (−1)n3nSolution. First we distribute the sum to obtain∞Xn=02n+ (−1)n3n=∞Xn=02n3n+∞Xn=0(−1)n3n=∞Xn=023n+∞Xn=0−13n.Since |23| < 1 and |−13| < 1, the geometric series formula tells us thatthe above is equal to11 −23+11 − (−13)=113+143= 3 +34=154.(7) Calculate the sum∞Xn=35nn + 3−5(n + 1)n + 45Solution. This is a telescoping series. For M ≥ 3 letSM=MXn=35nn + 3−5(n + 1)n + 4= 5MXn=3nn + 3−n + 1n + 4denote the M-th partial sum. The first four partial sums areS3= 536−47S4= 536−47+47−58S5= 536−47+47−58+58−69S6= 536−47+47−58+58−69+69−710Notice all terms cancel except the first positive term36that comesfrom plugging in n = 3 and the last negative term −M+1M+4that comesfrom plugging in n = M. ThereforeSM= 536−M + 1M + 4.Since limM→∞M+1M+4= 1, we have∞Xn=35nn + 3−5(n + 1)n + 4= limM→∞SM= 536− 1= −52.(8) Calculate the sum∞Xn=1ln(n + 1)n + 2−ln(n + 2)n + 3Solution. This is a telescoping series. For M ≥ 3 letSM=MXn=1ln(n + 1)n + 2−ln(n + 2)n + 36denote the M-th partial sum. The first four partial sums areS1=ln 23−ln 34S2=ln 23−ln 34+ln 34−ln 45S3=ln 23−ln 34+ln 34−ln 45+ln 45−ln 56S4=ln 23−ln 34+ln 34−ln 45+ln 45−ln 56+ln 56−ln 67Notice all terms cancel except the first positive termln 23that comesfrom plugging in n = 3 and the last negative term −ln(M+2)M+3thatcomes from plugging in n = M. ThereforeSM=ln 23−ln(M + 2)M + 3Using L’hopital’s rule, we find that limM→∞ln(M+2)M+3= 0, so we have∞Xn=1ln(n + 1)n + 2−ln(n + 2)n + 3= limM→∞SM=ln 23.(9) Consider the following sequences. Circle the correct answers belowand show all supporting work.(I)n(−1)nn2− 12n2+ 1o∞n=1(II)nln(n)no∞n=1(III)nln1no∞n=1Sequence (I) (converges / diverges )Solution. Recall the following theorem: Suppose {an}∞n=1is a se-quence of nonnegative numbers. If {an}∞n=1converges to 0, then thesequence {(−1)nan}∞n=1also converges to 0. Otherwise, {(−1)nan}∞n=1diverges. We haven2− 12n2+ 1≥ 07for n ≥ 1. Sincelimn→∞n2− 12n2+ 1=12is nonzero, it follows from the theorem that the sequence diverges.Sequence (II) ( converges / diverges)Solution. The limit limx→∞ln(x)xis an indeterminate form of type∞∞. By L’hopital’s rule, we havelimx→∞ln(x)x= limx→∞1xx= limx→∞1x2= 0.Thereforelimn→∞ln(n)n= 0,so the sequence converges.Sequence (III) (converges / diverges )Solution. We have limn→∞1n= 0. Since limx→0+ln(x) = −∞, thisshows thatlimn→∞ln1n= −∞,so the sequence diverges.(10) Consider the following sequences. Circle the correct answers belowand show all supporting work.(I)n(−1)nn2− 12no∞n=1(II)n(−1)nn2− 12n2o∞n=1(III)n(−1)nn ln(n)o∞n=1Sequence (I) ( converges / diverges)Solution. We haven2− 12n≥ 08for n ≥ 1. The limit limx→∞x2−12xis indeterminate of type∞∞. ByL’hopital’s rule, we havelimx→∞x2− 12x= limx→∞2xln(2)2x.The right-hand limit is also indeterminate of the same type. Apply-ing L’hopital’s rule again, we getlimx→∞2xln(2)2x= limx→∞2ln(2)22x= 0.Thereforelimn→∞n2− 12n= 0,so the sequence converges by the theorem mentioned in the solutionto (9) part (I).Sequence (II) (converges / diverges )Solution. We haven2− 12n2≥ 0for n ≥ 1. Sincelimn→∞n2− 12n2=12is nonzero, it follows that the sequence diverges.Sequence (III) (converges / diverges )Solution. We haven ln(n) ≥ 0for n ≥ 1. Since {n ln(n)}∞n=1diverges to ∞, it does not converge to0, so the sequence of interest diverges.9(11) Consider the following series. Circle the correct answers below andshow all supporting work.(I)∞Xn=1n2+ 14n3− 1n(II)∞Xn=12n(n!)(n2)Series (I) ( converges / diverges)Solution. Each term of this series is an n-th powers whose basedepends on n. Therefore we should use the root test. We havelimn→∞n2+ 14n3− 1n1/n= limn→∞n2+ 14n3− 1= 0,so this series converges by the root test.Series (II) ( converges / diverges)Solution. The presence of the factorial is a good sign that we shoulduse the ratio test. We havelimn→∞2n+1((n+1)!)((n+1)2)2n(n!)(n2)= limn→∞2n+12n·1(n+1)!1n!·1(n+1)21n2= limn→∞2 ·n!(n + 1)!·n2(n + 1)2= limn→∞2 ·1n + 1nn + 12= 0since limn→∞1n+1= 0 and limn→∞nn+12= 1. Therefore the seriesconverges by the ratio test.(12) Consider the

View Full Document Unlocking...